The influence of operating capital and cash holding on firm profitability - Ashfaq Habib; Muhammad Asif Khan; József Popp; Mónika Rákos (Economies, 2022)
This study analyzes the influence of operating capital on a firm's profitability in the manufacturing sector of China. The study investigates that operating capital develops a non-linear relationship with firm profitability by using the ordinary least square (OLS), fixed effect (FE), and generalized method of moments (GMM) regression. The research reveals that positive operating capital in financially less-constrained firms significantly negatively influences the firm's profitability. Conversely, negative operating capital in financially constrained firms significantly positively influences the firm's profitability. Further, we find that financially less-constrained firms design an efficient level of operating capital by holding positive operating capital and negative cash, while constrained firms design an efficient level of operating capital by holding negative operating capital and positive cash. Additionally, we also identify the optimal level of operating capital to increase the firm's profitability. Generally, we conclude that a firm can design a level of efficient operating capital by trading-off cash with non-cash assets.
Keywords: 330; operating capital; cash holding; financial constrained firms; less-constrained firms